CANE ADVISER: A MOBILE BASED APP FOR TRANSFER OF TECHNOLOGY IN SUGARCANE - Shanthy, Rajula; Alarmelu, S; Jayabose, C; Malathi, P; Ram, Bakshi (Journal of Sugarcane Research, 2020)
The information and communication support for sugarcane crop has been mainly conventional with limited personalized extension services to reach all the cane growers spread across the country. The diversity of agro ecological situations, varied technologies recommended and needs of sugarcane farmers further mount to this challenge. Information and Communication Technology and in particular mobile technologies are seen as a game changer in agriculture. It is commanding therefore for the sugarcane technology dissemination system operating across the states, to shift from being predominantly traditional, to harness the potentialities of information technology bridging the barriers of time and space. Keeping this in view, the ICAR-Sugarcane Breeding Institute of the Indian Council of Agricultural Research, has developed an interactive androidbased mobile app, Cane Adviser to serve to the needs of the stakeholders in sugarcane cultivation. The paper explains how Cane Adviser was developed methodically taking into account the information needs of theÂ target audience, deciding the various modules to be embedded in the app and how it was evaluated before hosting in google play store. Explaining the various particulars of the mobile app, the paper details the role of Cane Adviser in disseminating sugarcane technologies and timely delivery of information tailor-made to the cane growers and cane development personnel so as to get enhanced cane productivity